Kinerja Bappeda Kabupaten Banyuwangi dalam Penyusunan Rencana Kerja Pembangunan Daerah (RKPD); (Studi di Bappeda Kabupaten Banyuwangi) - Rahayu, Ribut; Makmur, Mochamad; Setyowati, Endah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This paper analyze the performance of Bappeda Banyuwangi Regency in making Local Development Action Plan 2015. Performance measurement of public sector organizations is relatively more difficult to do then the privat sector that having profit oriented. Value for money concept can be used for perfomance measurement in public sector. This research use economic measurement as one of the three subjects in value for money concept. It is consider about the cost of input procurement. Data taken from documentations and interviews. Result of the research show that performance of Bappeda Banyuwangi Regency in using of fund has fulfilled the economic criteria.